Effectiveness of a training program on improving the hand washing among children in primary schools - Mohamed Moussa, Maha; Abdella, Nabila Hassan Ali; Abu-Elenen, Nagwa Rizk Mohammed; Elkazaz, Rehab Hani (International Journal of Advanced Nursing Studies, 2015)
Background: Hand washing with soap has been viewed as one of the most cost-effective ways of reducing the global infectious disease burden. Proper hand washing technique is easy to learn and can significantly reduce the spread of infectious diseases among children. Aim: the study was conducted to evaluate the effectiveness of a training program on improving the hand washing among children in primary schools.Methods: quasi experimental design was used in the study. The data was collected from 450 students, aged 6 to 12 years. The study data were collected by a self-administered questionnaire sheet and observation checklist, the field data was collected in Port Said city elementary schools in six months periods.Results: The study concluded that there were highly significant statistical differences in total knowledge and practice score of the studied sample after implementation of educational program. Conclusion: Based on the findings of the current study, it is concluded that, the hand washing practices of children in primary schools was improved after the program implementation.